PENGARUH PROSEDUR PEMBERIAN KREDIT PEMILIKAN RUMAH SUBSIDI DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA REALISASI KREDIT DENGAN FASILITAS SUBSIDI BANTUAN UANG MUKA SEBAGAI VARIABEL INTERVENING - tommy munaf (EKONOMIKA, 2020)
This study aims to determine empirically the influence of the procedures for granting credit and good corporate governance on the performance of credit realization by subsidizing down payment assistance as an intervening variable. This study uses a sample of 107 employees at Bank BTN Tanjungpinang Branch. The data obtained were analyzed using "path analysis". The results of this study are the lending procedure has a direct and significant effect on the performance of credit realization with a path coefficient value of 0.183 and significant at 0.036 sig probability ≤ a = 0.05, good corporate governance direct and significant influence on the credit realization performance with a path coefficient of 0.188 and significant at 0.033 sig probability ≤ a = 0.05, lending procedure direct and significant influence on the subsidy for advance assistance with a path coefficient value of 0.312 and significant at sig 0.000 probability ≤ a = 0.05, good corporate governance direct and significant influence on money aid subsidies face with path coefficient value of 0.333 and significant at sig probability 0.000 ≤ a = 0.05, subsidy of advance cash assistance direct and significant influence on credit realization performance with path coefficient value of 0.641 and significant at sig probability 0.000 ≤ a = 0.05, pr Credit provision procedures have a significant effect on the performance of credit realization through subsidy for advance assistance which is an intervening variable with a coefficient value of 0.199> 0.183 direct coefficient value, good corporate governance has a significant effect on the performance of credit realization through subsidy for advance assistance which is an intervening variable with value coefficient 0.213> 0.188 direct coefficient value.